Genetic analysis of Italian patients with congenital tufting enteropathy. - d'Apolito, Maria; Pisanelli, Daniela; Faletra, Flavio; Giardino, Ida; Gigante, Maddalena; Pettoello-Mantovani, Massimo; Goulet, Olivier; Gasparini, Paolo; Campanozzi, Angelo (World J Pediatr, 2015)
BACKGROUND: Congenital tufting enteropathy (CTE), an inherited autosomal recessive rare disease, is a severe diarrhea of infancy which is clinically characterized by absence of inflammation and presence of intestinal villous atrophy. Mutations in the EpCAM gene were identified to cause CTE. Recent cases of syndromic tufting enteropathy harboring the SPINT2 (19q13.2) mutation were described. METHODS: Four CTE Italian patients were clinically and immunohistochemically characterized. Direct DNA sequencing of EpCAM and SPINT2 genes was performed. RESULTS: All patients were of Italian origin. Three different mutations were detected (p.Asp219Metfs*15, Tyr186Phefs*6 and p.Ile146Asn) in the EpCAM gene; one of them is novel (p.Ile146Asn). Two patients (P1 and P2) showed compound heterozygosity revealing two mutations in separate alleles. A third patient (P3) was heterozygous for only one novel EpCAM missense mutation (p.Ile146Asn). In a syndromic patient (P4), no deleterious EpCAM mutation was found. Additional SPINT2 mutational analysis was performed. P4 showed a homozygous SPINT2 mutation (p.Y163C). No SPINT2 mutation was found in P3. CLDN7 was also evaluated as a candidate gene by mutational screening in P3 but no mutation was identified. CONCLUSIONS: This study presented a molecular characterization of CTE Italian patients, and identified three mutations in the EpCAM gene and one in the SPINT2 gene. One of EpCAM mutations was novel, therefore increasing the mutational spectrum of allelic variants of the EpCAM gene. Molecular analysis of the SPINT2 gene also allowed us to identify a SPINT2 substitution mutation (c.488A>G) recently found to be associated with syndromic CTE subjects.